Вычислительные эксперименты по применению R-алгоритмов для решения одного класса задач нелинейного программирования - Лиховид, А.П. (Теорія оптимальних рішень, 2006)
The paper investigates the efficiency of r-algorithms used to mathematical programs with equilibrium constraints. The comparative computational results for SNOPT, LOQO, Ralg solvers with AMPL package on test problems from MacMPEC library are given.